Maximizing spring wheat productivity in the eastern Canadian Prairies II. Grain nitrogen, grain protein, and nitrogen use. (10th June 2022) - Mangin, Amy; Brûlé‐Babel, Anita; Flaten, Don; Wiersma, Jochum; Lawley, Yvonne
Abstract: The marketability of spring wheat ( Triticum aestivum L.) across the Canadian prairies is largely dependent on grain protein content. New high‐yielding cultivars require a large investment in fertilizer N to achieve milling quality standards. When high rates of N fertilizer are applied, N use efficiencies tend to decrease, lowering returns on investment. The objectives of this study were to identify patterns of N use for spring wheat cultivars and how they are influenced by agronomic management practices. Field trials were conducted in 2018 and 2019 in Manitoba, Canada, to evaluate N uptake timing, N remobilization from vegetative tissue and the resulting grain N yield and protein content. Three spring wheat cultivars were evaluated using five N fertilizer treatments with and without an application of a plant growth regulator (PGR). When high N rates were applied, average N use efficiency, for grain N production, was 60%. On average 21–36% of N uptake occurred after anthesis and this portion was highly dependent on late‐season precipitation. Targeting increases in early season N accumulation and grain‐fill remobilization, to produce optimal grain N levels, may be used to managing risk associated with unknown precipitation during the growing season. Cultivars tested produced similar grain N levels through fundamentally different N use patterns, indicating that there may be opportunity for breeding programs to target N use patterns that best fit environmental conditions of the Canadian prairies to maximize grain N production. Core Ideas: Twenty‐one to 36% of the N uptake by the crop occurred during the postanthesis period. Vegetative N remobilization was highly dependent on N accumulated at anthesis. Eighty percent of leaf N and 70% of stem N accumulated at anthesis was remobilized to the grain. Split N applications increased postanthesis N uptake, resulting in increased grain protein. Grain N accumulation and remobilization patterns are cultivar specific.